The Role of Electronic Qualifications and Extrinsic Rewards in Enhancing Internal Auditor Effectiveness: A Study in Bandung - Radit Agung (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to analyze the influence of electronic qualifications on the effectiveness of internal auditors, as well as examine the role of extrinsic rewards as a moderation variable in the relationship. The background of this research is based on the need for organizations to have auditors who are not only technically competent, but also externally motivated in dealing with the complexities of technology-based audits. The approach used in this study is quantitative, with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. The data was obtained through the distribution of questionnaires to internal auditors working in various public and private agencies in the city of Bandung, and measured using the Likert scale. The results of the study show that electronic qualifications have a positive and significant influence on the effectiveness of internal auditors. Similarly, extrinsic rewards have been shown to contribute to increasing the effectiveness of auditors' work. Furthermore, the findings show that extrinsic rewards moderates the relationship between electronic qualifications and auditor effectiveness, where highly qualified auditors will show more optimal performance when supported by an adequate reward system. This research provides theoretical and practical implications that the development of internal auditor competencies needs to be balanced with a proportionate and structured awarding strategy. Organizations are advised to design auditor resource management policies based on a combination of technical capacity building and motivational fulfillment to improve the effectiveness of internal audits on an ongoing basis.